2021
DOI: 10.1101/2021.10.04.463119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear genome of a pedinophyte pinpoints genomic innovation and streamlining in the green algae

Abstract: The genomic diversity underpinning high ecological and species diversity in the green algae (Chlorophyta) remains little known. Here, we aimed to track genome evolution in the Chlorophyta, focusing on loss and gain of homologous genes, and lineage-specific innovations of the Core Chlorophyta. We generated a high-quality nuclear genome for pedinophyte YPF701, a sister lineage to others in the Core Chlorophyta, and incorporated this genome in a comparative analysis with 25 other genomes from diverse Viridiplanta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…As an evolutionary plant biologist, I have enjoyed recent works on land plant evolution (de Vries & Archibald, 2018), the anatomy and evolution of lycopsid rooting structures (Hetherington & Dolan, 2016), the evolutionary success of ferns (McElwain, 2011) and discussion on the need for more nonseed plant model organisms (Rensing, 2017). Some of my favourite research papers include: studies by Xu et al (2022) and Repetti et al (2022) of the genome of Pedinomonas minor, identifying the genomic evolution of chlorophytes; analysis by Clark et al (2016) of the evolution of fern genome traits; the work by Barba-Montoya et al (2018) to constrain the timing of the diversification of angiosperms; and that of Brockington et al (2015) which found that lineage-specific radiations of key biosynthetic genes explain betalain pigmentation in the flowering plant order Caryophyllales. All of these inspiring works have helped to stimulate ideas and discussion, as well as providing excellent reviews of the literature.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%
“…As an evolutionary plant biologist, I have enjoyed recent works on land plant evolution (de Vries & Archibald, 2018), the anatomy and evolution of lycopsid rooting structures (Hetherington & Dolan, 2016), the evolutionary success of ferns (McElwain, 2011) and discussion on the need for more nonseed plant model organisms (Rensing, 2017). Some of my favourite research papers include: studies by Xu et al (2022) and Repetti et al (2022) of the genome of Pedinomonas minor, identifying the genomic evolution of chlorophytes; analysis by Clark et al (2016) of the evolution of fern genome traits; the work by Barba-Montoya et al (2018) to constrain the timing of the diversification of angiosperms; and that of Brockington et al (2015) which found that lineage-specific radiations of key biosynthetic genes explain betalain pigmentation in the flowering plant order Caryophyllales. All of these inspiring works have helped to stimulate ideas and discussion, as well as providing excellent reviews of the literature.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%
“…Over the past decade, the genomic data of several algal lineages have enabled us to gain detailed insights into their phylogeny, evolution, and adaption to changing environments (Delaroque & Boland, 2008; Worden et al ., 2009; H. Liang et al ., 2020; Li et al ., 2020; Wang et al ., 2020, 2021). A draft genome of an unidentified, marine pedinophyte was recently presented (Repetti et al ., 2022). The authors concluded that the relatively small genome of 27.9 Mb indicated positive selection for genome streamlining in this organism, independent of other Chlorophyta.…”
Section: Introductionmentioning
confidence: 99%